2013
DOI: 10.1088/2041-8205/769/2/l33
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Magnetic Reconnection Driven by Granular Scale Advection

Abstract: We report the first evidence of magnetic reconnection driven by advection in a rapidly developing large granule using high spatial resolution observations of a small surge event (base size ∼ 4 × 4 ) with the 1.6 m aperture New Solar Telescope at the Big Bear Solar Observatory. The observations were carried out in narrowband (0.5 Å) He i 10830 Å and broadband (10 Å) TiO 7057 Å. Since He i 10830 Å triplet has a very high excitation level and is optically thin, its filtergrams enable us to investigate the surge f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 20 publications
5
9
0
Order By: Relevance
“…We can trace their roots directly to the underlying photosphere and its magnetic field. With the help from the He I 10830 Å data and simultaneous high-resolution images of the photosphere, we report that these microeruptions are rooted in the area of intergranular lanes, which confirms previous results (Ji et al 2012;Zeng et al 2013;Wang et al 2021). Furthermore, they are situated on magnetic polarity inversion lines (PILs).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…We can trace their roots directly to the underlying photosphere and its magnetic field. With the help from the He I 10830 Å data and simultaneous high-resolution images of the photosphere, we report that these microeruptions are rooted in the area of intergranular lanes, which confirms previous results (Ji et al 2012;Zeng et al 2013;Wang et al 2021). Furthermore, they are situated on magnetic polarity inversion lines (PILs).…”
Section: Discussionsupporting
confidence: 89%
“…For a microeruption such as any of those in the present paper, a dark microeruption with or without a discernible microjet spire in He I 10830 Å images, high-resolution Hα or EUV images along with high-resolution magnetograms are needed to decide whether the microeruption is the product of a microfilament eruption. Aslo, many other works have been reported regarding how magnetic flux emergences and cancellations induce various recurring jets (e.g., Chae et al 1999;Zhang & Ji 2014;Liu et al 2016;Chifor et al 2008;Zeng et al 2013, for a more comprehensive review, see Raouafi et al 2016). Therefore, our observation supports the magnetic reconnection scenario for the two microjets.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The observations have revealed the smallest scale magnetic activities in inter-granular lanes of the photosphere with their brightening going up into the local transition region. The finding was confirmed by further analysis to the same data set or similar observations (Zeng et al 2013;Hong et al 2017;Yang et al 2019). In the most recent work, Ji et al (2020) reported a possible correlation between the perturbations of magnetic field and He I 10830 Å absorption, both have a quasi-periodic nature.…”
Section: Introductionsupporting
confidence: 78%
“…During the past few years, NST studies have focused on fast imaging (no polarimetry yet in the following science highlights). For example, they studied rather rare three-ribbon flares (Wang et al 2014), sunspot oscillations (Yurchyshyn et al 2015), flux emergence coupled with a jet (Zeng et al 2013;Vargas Domínguez et al 2014), the eruption of a flux rope (Wang et al 2015), and the connection between small-scale events in the photosphere and subsequent coronal emission . From observations of a C-flare, Zeng et al (2014) concluded that the He 1083 nm triplet is formed primarily by photoionization of chromospheric plasma followed by radiative recombination.…”
Section: Its Instrumentation Consists Of Fast Imaging (Eg Broadbandmentioning
confidence: 99%